Dynamics and interactions of soil moisture and temperature during degradation and restoration of alpine swamp meadow on the Qinghai-Tibet plateau - Ma, Guankui; Zhang, Yongkun; Li, Hang; Yang, Yongsheng; Li, Runjie (Frontiers in Environmental Science, 2025)
Soil temperature (ST) and soil moisture (SM) are two fundamental land surface variables that directly or indirectly affect the processes and functions of alpine ecosystems. To clarify dynamics and interactions of SM and ST during degradation and restoration of alpine swamp meadow, four successional stages of alpine swamp meadow (non-degraded, NG; Kobresia humilis-dominated degraded, DG1; bare soil/weed-type degraded, DG2; artificially restored, RE) were selected to measure SM and ST at 10, 20 and 30 cm depths with 30-minute time interval in 2021 and 2022. Results showed that: (1) With the degradation and restoration of alpine swamp meadow, SM at 10 cm depth decreased at first, and then increased significantly (p < 0.05), which was attributed to the role of vegetation coverage and soil organic carbon in soil evaporation and water holding capacity, respectively; (2) ST at various depths did not respond to diverse degradation and restoration stages of alpine swamp meadow (p > 0.05); (3) The relationships between ST and SM varied with seasons, with positive and negative linear correlation in spring and summer, and positive exponential correlation in autumn and winter (p < 0.01). The study of SM and ST at different degradation and restoration stages of alpine swamp meadow will provide theoretical support for the research of related ecological processes and functions of such ecosystem.